Effects of force field and design parameters on the exergy efficiency and fuel utilization of microfluidic fuel cells. (21st April 2020) - Ouyang, Tiancheng; Chen, Jingxian; Zhou, Feng; Lu, Jie; Xu, Peihang; Chen, Nan; Mo, Chunlan
Abstract: Microfluidic fuel cells (MFCs) are novel systems that satisfy the critical requirements of having small dimensions and substantial power output for use in portable devices. In this study, three-dimensional mathematical models of two types of MFCs (flow-over and flow-through) are developed, by coupling multiphysics consisting of microfluidic hydrodynamics, electrochemical reaction kinetics, and species transport of fluid. Moreover, gravity, exergy, and parametric sensitivity are studied, which have tremendous impact on fuel cell performance and have been frequently overlooked in previous literature. The reliability of the numerical model is demonstrated by the excellent consistency between simulation results and experimental data. First, a parametric analysis is conducted, which includes the design parameters and gravity effect. Following this, the fuel utilization and exergy efficiency are calculated for various design parameters. Finally, a sensitivity analysis is performed to evaluate the influence of the indicators on the cell performance. It is shown that a relatively stable performance is achieved with the flow-through MFC under interference from the external environment. The reactive sites of the flow-through MFC can be utilised effectively, whereas further promotion of the flow-over MFC is limited by its inherent drawback. In addition, the sensitivity analysis reveals that cell performance depends strongly on the flow rate and fuel concentration. The results can be beneficial for the investigation of cell performance optimization. Highlights: Exergy analysis is performed based on the 3-D multiphysics mathematical model. Reactant concentration and velocity distribution are influenced by gravity effect. The rotation angle plays a significant role in the performance of the flow-over MFC. A normalized sensitivity analysis is conducted to evaluate the impact of parameters. Graphical abstract: Image 1